Produksi Kitosan Secara Enzimatik oleh Bacillus Sampah Perikanan - Afifah, Kufah Nur; Koentjoro, Maharani Pertiwi; Prasetyo, Endry Nugroho (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
The ability of Bacillus sp. has been developed by isolation bacteria from fisheries waste to synthesis chitin deaetylase. This microorganism secretes extracellular chitin deacetylase and does not involve cell lysis. Chitin deacetylase has roles as bioconversion which converts chitin to chitosan with deacetylation N-acetylglucosamine residue in chitin. The bioconversion process of chitin into chitosan in this study is occured by Bacillus sp. B3, Bacillus sp. B5, Bacillus sp. B6, and Bacillus sp. B12 through deacetylation enzymatic which is isolated from fisheries waste. The protein component of crude enzyme was measured using Bradford methods with BSA (Bovine Serum Albumin) as standard. The enzyme was purified by ammonium sulfate precipitation. Chitin deacetylase was characterized by measuring isoelectric point, enzyme activity, and protein component. While the fungtional groups of chitosan had characterized by FTIR and measured degree of deacetylation chitosan. The highest enzyme activity was achieved by Bacillus sp. B12 through ammonium sulphate purification at 75-90% fraction is 345.21U/ml with protein content is 0.0512 mg/ml. Chitin deacetylase from fourth Bacillus sp. has an isoelectric point at pH 5. The highest degree of deacetylation chitosan is 67% and the termination of acetyl groups had confirmed by IR spectra.